Artificial intelligence‐powered decentralized framework for Internet of Things in Healthcare 4.0 - Puri, Vikram; Kataria, Aman; Sharma, Vishal (Transactions on emerging telecommunications technologies, 2024)
Remote patient monitoring and data management have gained much popularity in recent years because of their enhanced access to low‐cost healthcare services. A cloud‐based healthcare system provides numerous solutions for collecting patient data and offers on‐demand well‐managed reports to patients and healthcare providers. However, it equally suffers from single‐point failure, security, privacy, and non‐transparency issues with the data, impacting the continuity of the system. To resolve such concerns, this article proposes an artificial intelligence (AI)‐enabled decentralized healthcare framework that accesses and authenticates Internet of Things (IoT) devices and create trust and transparency in patient healthcare records (PHR). The mechanism is based on the AI‐enabled smart contracts and the conceptualization of the public blockchain network. Alongside this, the framework identifies the malicious IoT nodes in the system. The experimental analyses are performed on the real‐time test environment, and significant improvements are suggested in terms of device energy consumption, data request time, throughput, average latency, and transaction fee. An overview of the proposed decentralized setup for IoT in Healthcare 4.0 comprising IoT nodes (end users), clinic nodes (intermediates), and a hospital node (main hub).